Chemical constituents of ochreinauclea maingayii (Hook.F.) Ridsd. (Rubiaceae) / Norfaizah Osman - Osman, Norfaizah (2014)
A study of chemical constituents from the leaves and bark of Ochreinauclea maingayii (Hook. f.) Ridsd. from the family Rubiaceae has been carried out. Nine compounds were successfully isolated and purified by applying chromatography techniques such as column chromatography (CC), thin layer chromatography (TLC) and preparative thin layer chromatography (PTLC). The compounds were harmane 38, naucledine 5, cadamine 42, isodihydrocadambine 78, neonaucline 79, cinnamide 81, benzamide 80, blumenol A 75 and ursolic acid 73. Neonaucline 75 is a new compound from the leaves of this species. All structures were elucidated by the means of spectroscopic method; 1H, 13C NMR, 2D NMR (COSY, HMBC, HMQC, NOESY and DEPT), UV, IR and LCMS. The significant vasorelaxant activity (more than 80% relaxation) could be observed on rat aorta was observed for compound naucledine 5, cadamine 42 and neonaucline 79 after injection of each sample with 1 x 10-5 M.